Correlation between Changes of NT-Pro BNP and HS-Troponin I Level with Cardiotoxicity in Locally Advanced Breast Cancer After Three Cycles of Neoadjuvant CAF Chemotherapy - Cicilia Indriaty; Leonita Anniwati; J.Nugroho Eko Putranto; Desak Gede Agung Suprabawati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Chemotherapy with cyclophosphamide, adriamycin, and fluorouracil (CAF) regiment in patients with locally advanced breast cancer have a risk of cardiotoxicity. Cardiotoxicity examination standards using left ventricular ejection fraction (LVEF) by echocardiography are considered insensitive for detection of subclinical ventricular dysfunction. NT-pro BNP and Hs-Troponin I (hs-TnI) as cardiac biomarkers are expected to help detect early cardiotoxicity. This study intended to analyze the correlation between changes of NT-pro BNP and hs-TnI levels with cardiotoxicity in breast cancer after three cycles of chemotherapy.This was a cross-sectional observational study, conducted at the Dr. Soetomo General Hospital Surabaya. The subjects consisted of 23 breast cancer patients who underwent chemotherapy with CAF regiment. NT-proBNP and hs-TnI examination used CLIA methods (Immulite 1000, ADVIA Centaur TnI-Ultra). Cardiotoxicity based on decreased LVEF to more than 10% of the initial LVEF value using echocardiography. Significant increases in NT pro BNP and hs-TnI levels were obtained before and after treatment (p=0.000, p=0.002). A significant decrease in LVEF was obtained before and after treatment (p=0.000), but only 2 patients (8.7%) showed cardiotoxicity. There was no correlation between changes in NT-pro BNP and hs-TnI levels with changes in LVEF before and after chemotherapy (p=0.666 and r=0.095; p=0.254 and r=-0.28). There was no correlation between changes in NT-pro BNP and hs-TnI levels with cardiotoxicity, which was assessed based on LVEF reduction, in locally advanced breast cancer after three-cycles of chemotherapy with CAF regiment.